News from Hugh S. Taylor and Rudolf Ladenburg, September 19, 1939 - Bredig, Max Albert (1939)
Max Bredig (1902-1977) notes news provided by two men, Hugh S. Taylor (1890-1974) and Rudolf Ladenburg (1882-1952), concerning logistics for his father, Georg Bredig's (1868-1944) immigration to the United States. Taylor is to talk to the President of Princeton University on behalf of Bredig, and Ladenburg sees great difficulty in Bredig finding work at Princeton without personal contact with the University.
Keywords: Bredig, Max Albert, 1902-1977; Taylor, Hugh S. (Hugh Stott), 1890-1974; Emigration and immigration; Ladenburg, Rudolf Walter, 1882-1952; Princeton University